- Z = f(A,B,C) = + B + AB + AC

By using the rules of simplification and ringing of adjacent cells in order to make as many variables redundant, the minimised result obtained is B + AC+ - Z = f(A,B,C) = B
+ B + BC + A

By using the rules of simplification and ringing of adjacent cells in order to make as many variables redundant, the minimised result obtained is B + A

Return

To submit your questions and queries please click here: *Composed by David Belton - April 98*

Updated by Richard Bigwood 2005